1973
DOI: 10.1029/ja078i001p00133
|View full text |Cite
|
Sign up to set email alerts
|

Drift shell splitting by internal geomagnetic multipoles

Abstract: Computations on an 80–coefficient model of the earth's field illustrate the ‘topography’ of the magnetic equatorial surface (on which B · ∇B = 0) and the geometry of the drift shells of geomagnetically trapped particles. Individual terms in the spherical harmonic expansion (offset dipole coordinates) of the geomagnetic scalar potential V(γ, θ, ϕ) are either even or odd in cos θ, where θ = π/2 denotes the dipole equator. Terms that (unlike the dipole) are even in cos θ tend to ‘warp’ the equatorial surface, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The radial diffusion mechanism proposed by Roederer et al () for deeply inner‐belt electrons is conceptually analogous to the collisional transport process known as “neoclassical diffusion” in the theory of laboratory plasma tokamaks (Balescu, ; Galeev et al, ; Galeev & Sagdeev, , ; Rosenbluth et al, ). This is why we call the corresponding magnetospheric radial‐diffusion process neoclassical.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The radial diffusion mechanism proposed by Roederer et al () for deeply inner‐belt electrons is conceptually analogous to the collisional transport process known as “neoclassical diffusion” in the theory of laboratory plasma tokamaks (Balescu, ; Galeev et al, ; Galeev & Sagdeev, , ; Rosenbluth et al, ). This is why we call the corresponding magnetospheric radial‐diffusion process neoclassical.…”
Section: Introductionmentioning
confidence: 94%
“…The result in requires numerical computation of the same integral as for the particle's bounce period 2π/Ω 2 , which varies with φ 3 in a way that would be of interest in any case (cf. Roederer et al, ).…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the geometrical criterion defining the magnetic equatorial surface in the dipoledominated case [Roedeter et al, 1973] can be extended to provide a physical description-of trapping center surfaces, that is, the location of trapped particle populations in arbitrary magnetic field geometries. Thus this concept may well be applied to more realistic paleomagnetic field configurations in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…There also have been several significant theoretical papers on the drift motions of energetic particles in a distorted magnetosphere to produce driftshell splitting [Shabansky, 1971[Shabansky, ,1972ifosik, 1971;Antonova, 1972;Roederer, 1972;Schulz, 1972;Alekseyev, '973;Roederer et al, 1973). All the above papers discuss particles in guiding-center raolion along the field lines.…”
Section: The Inner Beltmentioning
confidence: 99%